Animal Husbandry in Sverdlovsk Region in 1953—1985 - V. N. Mamyachenkov; M. I. Lvova; E. S. Kulikova (Научный диалог)
The relevance of the work is due to the enduring theoretical and practical interest shown by Russian society in the historical period considered in the article. The novelty of the study is seen in the fact that the materials from the funds of one federal and two regional archives, some of which are introduced into scientific circulation for the first time are used in the article. It is emphasized that the period under study included a huge number of events that directly affected the state of the country’s agriculture, including husbandry. It is argued that by the beginning of the 20th century the Middle Urals already had a fairly developed livestock sector. Attention is focused on the fact that the husbandry sector of the region met the beginning of the study period with poor performance. The authors express their conviction that the personal subsidiary plot of citizens (PSP) played an important role in providing the population with livestock products throughout the study period. It is concluded that, despite all the vicissitudes and cataclysms, the average per capita consumption of the three most important husbandry products (meat, milk and eggs) among a significant part of the population of the region by the beginning of the 1970s had reached the level of scientifically based consumption norms.